Molecular distribution of wastewater from a meat by-products processing company, treated using a batch system (SBR) (2011)
ABSTRACT: Biological treatments of wastewater depend on the char-acteristics of organic matter. The molecular weight frac-tionation of the various components of wastewater is of great importance as it helps to design appropriate treat-ment technologies. The purpose of this study was to eval-uate the distribution of particle sizes present in two types of wastewater generated in a company that processes meat by-products and their respective mixtures. Evalua-tion was carried out before and after treatment using a dis-continuous system in a Sequencing Batch Reactor (SBR). The analysis in the tributaries of the system showed that most of the parameters analyzed had a molecular weight higher than 10,000 Da. The results of the effluents showed that the SBR system is adequate to remove a high frac-tion of readily biodegradable organic matter, achieving a removal order of 98.68%, 98.14% and 70.51% for COD, BOD5 and NH4+-N respectively.